A mobile bandwidth-aggregation reservation scheme for NEMOs - Wang, Jui-Tang; Hsu, Yuan-Ying; Tseng, Chien-Chao (My University, 2008)
A NEtwork that is MObile (NEMO) usually consists of at least one Mobile Router (MR) attached to the infrastructure to manage all external communication for of all nodes inside a NEMO. Because a NEMO moves as a whole, previous mobile ReSource reserVation Protocols have two problems in supporting quality of services (QoS) for NEMOs; that is, mobility unawareness and excessive signal overhead. In this paper, we first address these two problems and then propose a Mobile Bandwidth-Aggregation (MBA) reservation scheme to support QoS guaranteed services for NEMOs. In order to resolve these two problems, MBA makes an MR the proxy of all nodes insides a NEMO and has the MR aggregates and reserve the bandwidth required for all node inside a NEMO. Mathematical analysis and simulation results show that the proposed MBA scheme can significantly reduce the signal overhead for reservation maintenance. Furthermore we also present three hypothetic policies of tunnel reservations for NEMOs, and conduct simulation to evaluate these policies in terms of blocking probabilities and bandwidth utilizations.
Keywords: NEMO; mobile router; QoS; RSVP; MRSVP; HMRSVP